A new Concentric Circles Detection method for Object Detection applied to Radar Images. (27th February 2019) - Guerrero, José Miguel; Muñoz, Andreas; Santos, Matilde; Pajares, Gonzalo
Abstract : In this work, a new concentric circles detection method for object detection is proposed. It has been applied to the images of a commercial radar, captured with a Charge-Coupled Device (CCD) camera. The processing includes the detection of centres and concentric circles in the images and the identification of the radar scale. Several methods found in the literature have been applied and compared with our novel proposal for multiple concentric circles detection, called "Propagation Method based on Circular Regression". This methodology has been validated with real radar images, proving its efficiency in obtaining the distance of any object to a marine vessel, with high accuracy and low computational cost, in real time. This system can not only be applied to most existing radars in the market by adjusting the parameters of each model but our proposal for concentric circle detection can be also applied to other sensing applications.